REVOLUSI INDUSTRI, LEDAKAN PENDUDUK DAN MASALAH LINGKUNGAN - Baiquni, M (Jurnal Sains Dan Teknologi Lingkungan, 2009)
Our civilization has dractically changed since new scientific revolution led to technological inventions andaccelletared by industrial revolution. Human dominated to the nature. During industrial revolution thenumber of population has increased sharply and their lifestyle and consumption level has achieved certainlevel beyond that in the past. By the time natural resources is being exploited and environmental pollutionand degradation is becoming worse. Ironically human welfare is not distributed equally, social gaps arewide and conflicts often happen, which are related to moral degradation. The end of this paper is areflection on the human mandate to lead the world, Khalifah fil Ardh.Keywords: Industrial revolution, population changes and environmental degradation.